Reactive oxygen species signaling influences feeding behaviour - Lyngdoh, John Amote; Wahlang, Julie B.; Nongkynrih, Banylla (International Journal of Research in Medical Sciences, 2017)
Reactive Oxygen Species (ROS) are not just by products of substrate oxidation but also chemicals that are involved in intracellular signaling when they are generated transiently and moderately. This review explores the intracellular signaling aspects of reactive oxygen species in influencing feeding behaviour. Substrates like glucose and lipids stimulate generation of reactive oxygen species mainly through mitochondria and to some extent through the NADPH oxidases. The level of ROS generated in hypothalamic neurons like NPY/AgRP and POMC neurons, under the influence of substrate level, directly influences the activity of these neurons and subsequently affect the downstream neurons located in other parts of the hypothalamus like the ventromedial nucleus (VMN), the paraventricular nucleus (PVN) and the lateral hypothalamus. Activation of POMC neuronal population is driven by increase ROS level whereas activation of NPY/AgRP neurons occurs when ROS level is reduced. The activation of these neurons will determine the feeding behaviour which will either be satiety if POMC neurons are activated or increase food intake if NPY/AgRP neurons are activated.